Using video calls to study children's conversational development: The case of backchannel signaling - Bodur, Kübra; Nikolaus, Mitja; Prévot, Laurent; Fourtassi, Abdellah (Frontiers in Computer Science, 2023)
Understanding how children’s conversational skills develop is crucial for understanding their social, cognitive, and linguistic development, with important applications in health and education. To develop theories based on quantitative studies of conversational development, we need (i) data recorded in naturalistic contexts (e.g. child-caregiver dyads talking in their daily environment) where children are more likely to show much of their conversational competencies, as opposed to controlled laboratory contexts which typically involve talking to a stranger (e.g., the experimenter); (ii) data that allows for clear access to children’s multimodal behavior in face-to-face conversations; and (iii) data whose acquisition method is cost-effective with the potential of being deployed at a large scale to capture individual and cultural variability. The current work is a first step to achieve this goal. We built a corpus made of video chats involving children in middle childhood (6-12 years old) and their caregivers using a weakly structured word-guessing game to prompt spontaneous conversation. The manual annotations of these recordings have shown the similarity of the frequency distribution of multimodal communicative signals from both children and caregivers. As a case study, we capitalize on this rich behavioral data to study how both verbal and non-verbal cues contribute to the development of conversational coordination. In particular, we looked at how children learn to engage in coordinated conversations not only as speakers but also as listeners by analyzing children’s use of backchannel signaling (e.g., verbal 'mh' or head nods) during these conversations. Contrary to results from previous in-lab studies, our use of both more natural/spontaneous conversational settings and more adequate controls allowed us to reveal that school-age children are strikingly close to adult-level mastery in many measures of backchanneling. Our work demonstrates the usefulness of recent technology in video calling for acquiring quality data that can be used for research on children’s conversational development in the wild.